Synthesis and characterization of nickel selenide thin films deposited by chemical method - Hankare, P. P.; Jadhav, B. V.; Garadkar, K. M.; Chate, P. A.; Mulla, Imtiaz S.; Delekar, S. D. (Journal of Alloys and Compounds, 2010)
Nickel selenide thin films have been deposited using chemical bath method on non-conducting glass substrates in a tartarate bath containing nickel sulphate octahydrate, hydrazine hydrate, sodium seleno-sulphate in an aqueous alkaline medium. The grown films were uniform, well adherent and black in color. The films were characterized using X-ray diffraction, scanning electron microscopy, optical absorption and electrical measurements. The nickel selenide thin film revealed polycrystalline nature with hexagonal system. The direct optical band gap of the film was found to be 1.61 eV. Electrical resistivity of film was observed in the order of 10(3) (Omega cm) with p-type conduction mechanism. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Semiconductors; Thin films; X-ray diffraction

Synthesis and characterization of chemically deposited nickel substituted CdSe thin film - Hankare, P. P.; Jadhav, B. V.; Chate, P. A.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2011)
The technologically important Cd(0.5)Ni(0.5)Se thin film has been developed by solution growth technique on non-conducting glass substrate in tartarate bath containing Cd(+2), Ni(+2) ions and sodium selenosulphate in an aqueous alkaline medium at room temperature. Various preparative conditions of the thin films are outlined. The films were characterized by X-ray diffraction, scanning electron microscope, optical absorption and electrical measurements. The X-ray diffraction study indicates that the film is polycrystalline in nature with hexagonal phase. Scanning electron micrograph shows that the film is homogeneous with well-defined grains. The films have high optical absorption coefficient. Thermoelectric power measurement shows p-type conduction mechanism. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Crystal growth; Electrical conductivity; thin film